Exploring the Role of News Outlets in the Rise of a Conspiracy Theory: Hydroxychloroquine in the Early Days of COVID-19 - Robert Dickinson; Dominique Makowski; Harm van Marwijk; Elizabeth Ford (COVID)
Improper use of hydroxychloroquine to treat COVID-19 has been linked to 17,000 preventable deaths. This content analysis study investigates the emergence of this conspiracy theory, the role of the news media in perpetuating and disseminating it, and whether coverage differed by outlet political alignment. We searched Nexis for relevant media from 17–31 March 2020. A total of 128 media pieces were coded qualitatively and thematically analysed. The news media amplified the voices of right-wing political elites and used a variety of manipulative tactics in reporting on hydroxychloroquine. Powerful ingroup/outgroup mechanisms polarised the American public and created a schism between Trump supporters and the public health apparatus that reflected the political asymmetry in reporting on hydroxychloroquine. The widespread use of optimistic framings and anecdotal evidence contributed to public misunderstandings of the evidence. Therefore, strategic and interventionist public health efforts are required to combat misinformation. This study informs discussions of how politicised media coverage catalyses conspiracism.